The Influence of Employee Empowerment, Psychological Capital, and Work-Family Conflict on Employees Commitment at the A. Yani Islamic Hospital Surabaya - Berliana Oktavia Setyawati; Eka Nurul Hidayah Puspa Seruni; Nyoman Anita Damayanti; Dewi Retno Suminar; Thinni Nurul Rochmah (Window of Health : Jurnal Kesehatan, 2025)
The low commitment of employees at A. Yani Islamic Hospital Surabaya is indicated by the high percentage of employees leaving the hospital for personal reasons. In 2017, it was 5.50%; in 2018, it was 6.57%; and in 2019 it was 10%. This study analyzes the relationship between employee empowerment, psychological capital, and work-family conflict on employee commitment at A. Yani Islamic Hospital Surabaya. The type of this research is an observational analytical study with a cross-sectional approach. The number of respondents in this study is 199 employees of A. Yani Islamic Hospital, who were randomly selected. Primary data collection was conducted through questionnaire completion to identify employee empowerment, psychological capital, and work-family conflict on employee commitment. Employee empowerment is measured using the CWEQ-II (Conditions of Work Effectiveness Questionnaire II), psychological capital is measured using the PCQ (Psychological Capital Questionnaire), work-family conflict is measured using the work-family conflict scale, and employee commitment is measured using the OCQ (Organizational Commitment Questionnaire). (Organizational Commitment Questionnaire). Data was processed using SPSS and analyzed using multiple linear regression. The research results show that employee empowerment (p=0.047), psychological capital (p=0.000), and work-family conflict (p=0.000) significantly affect employee commitment. The higher the employee empowerment and psychological capital, the higher the employee commitment. The lower the work-family conflict, the higher the employee commitment. The advice that can be given is to create a positive work situation, create a supportive work environment, provide positive feedback, and support employees in their personal development.